2021
DOI: 10.1007/s00068-021-01771-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcome of isolated lateral malleolar fracture treatment is independent of hospital trauma volume or teaching status: a nationwide retrospective cohort study

Abstract: Introduction In light of current discussions about centralisation and teaching in medicine, we wanted to investigate the differences in in-hospital outcomes after surgical treatment of isolated ankle fractures, taking into account high-volume centres (HVCs) and low-volume centres (LVCs) and teaching procedures. Methods A retrospective analysis of malleolar fractures recorded in a National Quality Assurance Database (AQC) from the period 01-01-1998 to 31-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Similar to our study, other researchers found that the duration of surgery is an independent risk factor for complications [ 21 , 30 ]. Louie et al found that resident involvement per se is not a significant risk factor in malleolar fractures [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, other researchers found that the duration of surgery is an independent risk factor for complications [ 21 , 30 ]. Louie et al found that resident involvement per se is not a significant risk factor in malleolar fractures [ 21 ].…”
Section: Discussionsupporting
confidence: 92%